Plasticity‐related gene 1 is important for survival of neurons derived from rat neural stem cells. Issue 11 (30th August 2013) - Hashimoto, Tomio; Yamada, Misa; Iwai, Takashi; Saitoh, Akiyoshi; Hashimoto, Eri; Ukai, Wataru; Saito, Toshikazu; Yamada, Mitsuhiko
<x xml:space="preserve">Abstract</x> Plasticity‐related gene 1 (Prg1) is a membrane‐associated lipid phosphate phosphatase. In this study, we first investigated the role of Prg1 in the survival of neurons derived from rat neural stem cells (NSCs) using small interfering RNA (siRNA). Prg1 knock‐down decreased the cell number. Interestingly, Prg1 knock‐down increased genomic DNA fragmentation, suggesting the possible induction of apoptosis. Exogenously expressed Prg1 rescued the cells from death and restored the loss of 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide (MTT) activity induced with Prg1 siRNA. However, exogenously expressed mutated‐Prg1 (the 253rd amino acid, histidine253, had been changed to alanine) did not rescue the cell death or restore the MTT activity. Histidine253 of Prg1 has been reported to be important for lipid phosphate phosphatase activity. These results suggest that Prg1 is important for survival of neurons through its dephosphorylation activity. © 2013 Wiley Periodicals, Inc.